Az illegális migráció alakulása Csongrád megyében 2008-2010 - Lukács János (Szegedi Tudományegyetem Állam- és Jogtudományi Kar Szeged, 2012)
One of the most important tasks of all states is to provide adequate safety for their citizen. The free movement at the external borders has been and is permitted by the schengen member states so that they still provide criminal, social and economical safety against the violation of law coming beyond the borders. First of all, these are achieved by the aggravation of border protection, severe border traffic and complex in-depth controls in those countries located along the external borders. The exquisite execution of the compound tasks are helped directly with finance and technical devices. In the meantime, the efficiency of fulfilment is checked by on the spot examinations. The intention is obviously to take an effective action against terrorism and the trafficking of goods, weapons and human beings through the maintenance of illegal immigration. Csongrád county can be considered as the gate of Balkans of the European Union. Despite the harsh pressure of immigration, the local authorities in a close cooperation developed with the partner organizations execute their border- and aliens policing tasks effectively, which were taken under their authority. The expectations are severe, since we have to correspond equally to the requirements established by the population of the region, the country and the European Union.
Keywords: Társadalomtudományok; Szociológia; Jogtudomány